PML body meets telomere: The beginning of an ALTernate ending? - Chung, Inn (Landes Bioscience, 2012)
The unlimited proliferation potential of cancer cells requires the maintenance of their telomeres. This is frequently accomplished by reactivation of telomerase. However, in a significant fraction of tumors an alternative lengthening of telomeres (ALT) mechanism is active. The molecular mechanism of the ALT pathway remains elusive. In particular, the role of characteristic complexes of promyelocytic leukemia nuclear bodies (PML-NBs) with telomeres, the ALT-associated PML-NBs (APBs), is currently under investigation. Here, we review recent findings on the assembly, structure and functions of APBs. It is discussed how genomic aberrations in ALT-positive cancer cells could result in the formation of APBs and in ALT activity. We conclude that they are important functional intermediates in what is considered the canonical ALT pathway and discuss deregulations of cellular pathways that contribute to the emergence of the ALT phenotype.